Rice PROTEIN l‐ISOASPARTYL METHYLTRANSFERASE isoforms differentially accumulate during seed maturation to restrict deleterious isoAsp and reactive oxygen species accumulation and are implicated in seed vigor and longevity. Issue 2 (14th March 2016) - Petla, Bhanu Prakash; Kamble, Nitin Uttam; Kumar, Meenu; Verma, Pooja; Ghosh, Shraboni; Singh, Ajeet; Rao, Venkateswara; Salvi, Prafull; Kaur, Harmeet; Saxena, Saurabh Chandra; Majee, Manoj
Summary: PROTEIN l ‐ISOASPARTYL O ‐METHYLTRANSFERASE (PIMT) is a protein‐repairing enzyme involved in seed vigor and longevity. However, the regulation of PIMT isoforms during seed development and the mechanism of PIMT‐mediated improvement of seed vigor and longevity are largely unknown. In this study in rice ( Oryza sativa ), we demonstrate the dynamics and correlation of isoaspartyl (isoAsp)‐repairing demands and PIMT activity, and their implications, during seed development, germination and aging, through biochemical, molecular and genetic studies. Molecular and biochemical analyses revealed that rice possesses various biochemically active and inactive PIMT isoforms. Transcript and western blot analyses clearly showed the seed development stage and tissue‐specific accumulation of active isoforms. Immunolocalization studies revealed distinct isoform expression in embryo and aleurone layers. Further analyses of transgenic lines for each OsPIMT isoform revealed a clear role in the restriction of deleterious isoAsp and age‐induced reactive oxygen species (ROS) accumulation to improve seed vigor and longevity. Collectively, our data suggest that a PIMT‐mediated, protein repair mechanism is initiated during seed development in rice, with each isoform playing a distinct, yet coordinated, role. Our results also raise the intriguing possibility that PIMT repairs antioxidative enzymes and proteins which restrict ROS accumulation, lipid peroxidation, etc. in seed, particularly during aging, thus contributing to seed vigor and longevity.